The Impact of Movement Control Orders on Malaysian School Administrators during COVID-19 - Mohammad, Nazeri; Yusof, Siti Ilyana Mohd (ASEAN Journal of Educational Research and Technology, 2023)
The COVID-19 problem has the potential to change our planet and our global outlook. It could also inform us about how education needs to evolve to better prepare our young students for the future. For the time being, educators all across the world are debating the necessity to rethink how future generations will be educated. This could simply be a disruption that forces us to reconsider how we educate and ask ourselves what should be taught and what we should be preparing our students for. In the future decades, successful people will need to be able to recognize this interconnectedness and traverse across boundaries to leverage their uniqueness and collaborate globally. As educators struggle to find new ways to communicate with students outside of the classroom, now is a good opportunity to consider how these disruptive crises might help us define what learning should include. What adjustments would have to be made in school administrators' preparation if the focus of their training switched to assisting them in more consciously selecting the lenses that guided their school change efforts?